Territoriale Culten in West-Congo: verdwijning of transformatie? - Vanhee, Hein (Afrika Focus, 1998)
This paper discusses some of the key issues in my current research on the history of the relationship between society, tradition and Christianity in the west of Congo-Kinshasa over the last century. My focus here is on the process of progressive transformation of the nineteenth-century territorial cults and the structural continuity which is apparent in the development of the Congolese Christian church in the area. In presenting some of my working hypotheses I am suggesting that after an initial period of open hostility towards the first missionaries, BaKongo became aware - ’empirically’ as it were - of the fact that new ways were to be explored in order to compete with the challenges of Western colonialism and the forces of modernity and globalisation. In this regard, the history of religious life in West Congo can be described as a progressive attempt to regain control over the relations between human society and the supernatural world. KEY WORDS: African Christiantity, Central Africa, religion, territorial cults